S.IBRAGIMOV POEZIYASÍNDA TÁBIYAT TEMASÍNÍŃ SÚWRETLENIWI - Qosbergenova, Aysanem Muratbaevna (SCIENCE and SOCIETY, 2026)
The article analyzes the features of the artistic and philosophical depiction of the theme of nature in the works of S.Ibragimov. The article analyzes the symbolic meanings of nature images, elements of modernist poetics, their connection with Eastern mystical thought, and the poet’s unique style based on examples. In addition, in the poetry of S.Ibragimov, the aesthetic function of the images of water, spring, wind, desert, bird and plant, their harmony with the spiritual world of man is revealed.